The degree of use of quality standards in programs provided for students with learning difficulties in the First Zarqa Education Directorate from the point of view of teachers - Bany Issmail, Marwan Qassem Ebrahem (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to identify the degree of use of quality standards in programs offered to students with learning difficulties. The study population consisted of all teachers of learning resource rooms in the schools of the First Directorate of Education in Zarqa Governorate, and they numbered (146) male and female teachers. The study sample was chosen randomly (stratified sample). The number of them is (60) male and female teachers Among them were (30) male and (30) female teachers. After reviewing the literature, arithmetic means, standard deviations, and the T-test were used. The results of the study indicated that the teachers saw the use of quality standards as moderate. (3.57) The averages ranged from (3.56 to 3.57) The results of the study also concluded that there were no statistically significant differences between the teachers. And parameters in the use of quality standards.
Keywords: learning difficulties; quality standards